DIRECT DATING OF HYDROTHERMAL W MINERALIZATION: U-PB AGE FOR HUBNERITE (MNWO4), SWEET HOME MINE, COLORADO - Romer R.L.; Luders V. (My University, 2006)
We have investigated the potential of hubnerite for U-Pb dating. Hubnerite forms typically at medium to low-temperatures in a wide range of pneumatolytic-hydrothermal mineral deposits, particularly porphyry molybdenum and Sn-specialized granites. Hubnerite from the Sweet Home Mine (Alma, Colorado) formed in a Pb-rich, U-poor environment, but still developed relatively radiogenic Pb isotopic compositions. The low Pbcommon contents in hubnerite (0.075 to 0.155 ppm) demonstrate that Pb is efficiently excluded from the crystal lattice. In contrast, U may substitute for Mn. The U-Pb data of h?bnerite scatter. Most of the scatter originates from samples with 206Pb/204Pb values below 50, where Pbblank contributes up to 30% to Pbtotal. Using the least radiogenic galena Pb, samples with 206Pb/204Pb values above 70 have overlapping 206Pb*/238U and 207Pb*/235U values and yield a 206Pb/238U age of 25.7 ? 0.3 Ma (2?). Late stage apatite from the Sweet Home Mine yields a 206Pb/204Pb-238U/204Pb isochron corresponding to an age of 24.8 ? 0.5 Ma (2?). A comparison of the U-Pb h?bnerite ages with literature 40Ar/39Ar ages on earlier sericite and the U-Pb age on later apatite suggests that (i) h?bnerite yields accurate U-Pb ages and (ii) the evolution of the Sweet Home mineralization from greisen-type mineralization to medium-temperature hydrothermal vein mineralization took place in a few hundred thousand years at most. Aqueous low-N2-bearing and aqueous inclusions in the dated hubnerite have homogenization temperatures between 325 and 356 °C and moderate salinity (up to 6.7 wt% NaCl equiv.). Thus, hubnerite represents one of the rare examples of a mineral that can be dated accurately and carries petrological information.
Keywords: GEOCHRONOLOGY; HYDROTHERMAL DEPOSIT; ISOTOPIC COMPOSITION; MINERALIZATION; PETROLOGY; TUNGSTEN; URANIUM-LEAD DATING; COLORADO; SWEET HOME MINE; ALMA